Comparative Efficacy of Chinese Herbal Injections for Treating Severe Pneumonia: A Systematic Review and Bayesian Network Meta-Analysis of Randomized Controlled Trials - Niu, Liqing; Xiao, Lu; Zhang, Xuemin; Liu, Xuezheng; Liu, Xinqiao; Huang, Xianglong; Zhang, Mingzhu (Frontiers in Pharmacology, 2022)
Background: Severe pneumonia (SP) has a high mortality rate and is responsible for significant healthcare costs. Chinese herbal injections (CHIs) have been widely used in China as a novel and promising treatment option for SP. Therefore, this study assessed and ranked the effectiveness of CHIs to provide more sights for the selection of SP treatment. Method: Seven databases were searched from their inception up to April 1, 2021. The methodological quality of included study was evaluated by the Cochrane risk-of-bias tool. Then, a Bayesian network meta-analysis (NMA) was performed by OpenBUGS 3.2.3 and STATA 14.0 software. The surface under the cumulative ranking curve (SUCRA) probability values were applied to rank the examined treatments. A clustering analysis was utilized to compare the effect of CHIs between two different outcomes. Results: A total of 64 eligible randomized controlled trials (RCTs) involving 5,904 participants were identified for this analysis. Six CHIs including Xuebijing injection (XBJ), Tanreqing injection (TRQ), Reduning injection (RDN), Xiyanping injection (XYP), Shenfu injection (SF), and Shenmai injection (SM) were included. The results of the NMA showed that XBJ [odds ratio (OR) = 0.24, 95% credible interval (CI): 0.19, 0.30], TRQ (OR = 0.22, 95% CI: 0.12, 0.37), RDN (OR = 0.29, 95% CI: 0.04, 0.94), and SM (OR = 0.27, 95% CI: 0.08, 0.63) combined with conventional Western medicine (WM) improved the clinical effective rate more significantly than WM alone. Based on SUCRA values, TRQ + WM (SUCRA: 66.4%) ranked the highest in improving the clinical effective rate, second in four different outcomes, and third in only one. According to the cluster analysis, TRQ + WM exerted a positive effect on improving the efficacy of SP. As for safety, less than 30% (18 RCTs) of the included studies reported adverse drug reactions/adverse drug events (ADRs/ADEs), including 14 RCTs of XBJ, 3 RCTs of TRQ, and 1 RCT of RDN. Conclusion: In conclusion, the study found that the CHIs as co-adjuvant therapy could be beneficial for patients with SP. TRQ + WM showed an outstanding improvement in patients with SP considering both the clinical effective rate and other outcomes. Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/], identifier [CRD42021244587].